Swallowing Outcomes in Elderly Patients following Microvascular Reconstruction of the Head and Neck - Worley, Mitchell L; Graboyes, Evan M; Blair, Julie; Momin, Suhael; Armeson, Kent E; Day, Terry A; Huang, Andrew T (Otolaryngology-head and neck surgery, 2018)
Objective To describe swallowing outcomes in elderly patients undergoing microvascular reconstruction of the upper aerodigestive tract and identify risk factors for poor postoperative swallowing function. Study Design Case series with chart review. Setting Academic medical center. Subjects and Methods Sixty-six patients aged ≥70 years underwent microvascular reconstruction of the upper aerodigestive tract. The primary outcome measure was the Functional Oral Intake Scale (FOIS); preoperative and postoperative scores were dichotomized to define "good swallowing" and "poor swallowing." Logistic regression was performed to identify risk factors for poor postoperative swallowing function. Results In total, 91% of reconstructions were performed for oncologic defects. The most common defect site was the oral cavity (67%), and the anterolateral thigh (29%) was the most frequently used donor site. At 3-year follow up, 75% of patients had good swallowing function with 95% of patients who achieved good swallowing function doing so within 6 months of surgery. On multivariable analysis, patients with pT4 tumors (odds ratio [OR], 5.2; 95% confidence interval [CI], 1.0-25.6) and those undergoing at least partial glossectomy (OR, 4.7; 95% CI, 1.1-20.7) were more likely to experience poor swallowing function at 6-month follow-up. Conclusion Approximately half of elderly patients achieve good swallowing function within 6 months following microvascular reconstruction of the upper aerodigestive tract. Elderly patients with pT4 tumors and those requiring glossectomy are at highest risk for poor swallowing outcomes. These data can be used to inform preoperative patient counseling and design interventions aimed at improving swallowing function in those at high risk for poor outcomes.